Adipokinetic hormone-induced antioxidant response in Spodoptera littoralis - Večeřa, Josef; Krishnan, Natraj; Mithöfer, Axel; Vogel, Heiko; Kodrík, Dalibor (Comparative biochemistry and physiology. C. Toxicology & farmacology, 2012)
The antioxidative potential of the Manduca sexta adipokinetic hormone (Manse-AKH) in the last instar larvae of Spodoptera littoralis (Noctuidae, Lepidoptera) was demonstrated after exposure to oxidative stress (OS) elicited by feeding on artificial diet containing tannic acid (TA). Determination of protein carbonyls (PCs) and reduced glutathione (GSH) levels, monitoring of activity of antioxidant enzymes catalase (CAT), superoxide dismutase (SOD) and glutathione-S-transferases (GSTs), as well as measuring of the mRNA expression of CAT and SOD were used as markers of the OS. Injection of the Manse-AKH (5 pmol per individual) reversed the OS status by mitigation of PCs formation and by stimulation of glutathione-S-transferases (GSTs) activity. The CAT and SOD mRNA expression was significantly suppressed after the Manse-AKH injection while activity of these enzymes was not affected. These results indicate that diminishing of OS after the AKH injection might be a result of activation of specific enzymatic pathway possibly at the post-translational level rather than a direct effect on regulation of antioxidant marker genes at the transcriptional level.
Keywords: Oligopeptides; Animals; Gene Expression Regulation, Enzymologic; katalasa; Pyrrolidonecarboxylic Acid; Superoxide Dismutase; Antioxidants; regulace genové exprese enzymů; glutathion; oxidační stres; Catalase; Manduca; kyselina pyrrolidonkarboxylová; taniny; Glutathione; superoxiddismutasa; Oxidative Stress; glutathiontransferasa; oligopeptidy; hmyzí hormony; Glutathione Transferase; hmyzí proteiny; polymerázová řetězová reakce s reverzní transkripcí; dieta; Diet; Reverse Transcriptase Polymerase Chain Reaction; Insect Hormones; Spodoptera; antioxidancia; Insect Proteins; Larva; zvířata; Tannins; larva